Information Warfare Forging Communication Strategies for Twenty-First Century Operational Environments - Farwell, James P. (Marine Corps University Press (MCUP), 2020)
Great political and military leaders understand that communication strategies are key to victory in any conflict. Seizing the narrative can enable victory while failure to do so yields that advantage to the adversary. Gone are the days when competing armies confronted one another across battlefields. The information environment has made engagements and conflict both local and global all at once such that- as never before-information warfare is critical to victory. Understanding culture, history, local political dynamics, the interactions of different players, and the need to forge cohesive communication plans at the strategic, operational, and tactical levels matters more than ever to commanders and operators. In Information Warfare, James P. Farwell describes how commanders and operators must and can define winning outcomes and the strategies, operations, and tactics to achieve them. He lays out concrete, actionable steps to get results and places them in historical context, then provides a workbook to assist readers in devising communication strategies that produce victory in the sphere of information warfare.